REFLECTIONS ON TEACHING PRACTICE IN BASIC EDUCATION IN THE LIGHT OF THE BNCC: IMPACTS ON THE CURRICULUM AND TEACHER TRAINING - Maria da Silva, Josina; Berto Silva, Gledson; Edjanir Cândido Pereira, Maria; Margarete do Nascimento Mendonça, Maria; Holond de Lima Rocha, Kleyton; Maria Monteiro da Silva, Gilvana; José Melo dos Santos, Mozart; Carlos Vanderlei da Silva, José; da Silva Lima, Almir; Cristina Sousa, Maryone (Revista Gênero e Interdisciplinaridade, 2024)
This article proposes a reflection on teaching practice in Basic Education in light of the National Common Curricular Base (BNCC) and its impacts on the curriculum and teacher training. The BNCC, as the guiding document for education in Brazil, establishes the essential knowledge, skills and abilities that all students must develop throughout basic education. In this context, the role of the teacher is fundamental, as he is the mediator between the content proposed by BNCC and his pedagogical practice. The objective of this work is to analyze how the BNCC influences teaching practice, considering the challenges and possibilities that arise from this relationship. To this end, a bibliographical review was carried out on the BNCC, teacher training and pedagogical practice in basic education. The results indicate that the BNCC has significant impacts on the school curriculum and teacher training, requiring a reorganization of educational practices and greater attention to the skills and abilities that must be developed by students. In view of this, it is concluded that it is essential to rethink teacher training and pedagogical practice, seeking greater articulation between BNCC content and teaching methodologies, in order to guarantee quality education aligned with the demands of contemporary society.